Keterlibatan Pelanggan, Ekuitas Pelanggan, dan Niat Beli Ulang Pada Aplikasi Seluler - Cahyo Adi Utomo; Septilita Ibau; Ellyawati J (Jurnal of Management and Social Sciences, 2023)
This study aims to examine the effect of customer engagement, customer equity, purchase intention on Cellular Applications. Those used in this study were women and men who had made transactions/purchases of mobile applications. The number of samples in this study were 250 respondents, with the provisions of 205 men and 45 women. The data for this study were collected by distributing questionnaires through an online survey system using the Google form. The data analysis technique used in this study uses the PLS-SEM analysis technique with the SmartPLS program to test the hypothesis. The results of this study indicate that customer involvement has no significant effect on repurchase. That is, enthusiasm in visiting the mobile application may not necessarily attract the attention of customers to decide on a purchase because there are customers who are usually just for fun to see and compare prices and calculate the total price with postage and other additional costs. Besides that, this study also shows that the quality of information has a positive and significant influence on repurchase. Therefore, it can be concluded that the more complete and accurate the availability of this information, if it is appropriate and can solve problems for its customers, the higher the opportunity for customers to make repeat purchases from the same product and service providers.